On the colour types in Lycodes nakamurae (Tanaka, 1914) and species composition of the subgenus Furcimanus (Perciformes: Zoarcidae: Lycodes) in the Sea of Japan - Saveliev, Pavel A.; Balanov, Andrey A.; Kukhlevskii, Andrey D. (Zootaxa, 2014)
Two colour types were revealed in a zoarcid fish of the subgenus Furcimanus, genus Lycodes, in the Sea of Japan. A comparison of morphometric, meristic and genetic characters in dark coloured and light coloured individuals suggests that the two colour morphs represent a single species, determined to be Lycodes nakamurae (Tanaka, 1914). Variability in colouration within L. nakamurae and a lack of morphological or molecular characters distinguishing L. nakamurae from L. nishimurai Shinohara & Shirai, 2005 suggest that the latter should be considered a synonym of L. nakamurae (Tanaka, 1914). A record of L. pectoralis in the waters of the Republic of Korea is regarded as a misidentification. Thus, we conclude that only one species of the Lycodes subgenus Furcimanus, L. nakamurae, with dark and light colour morphs as well as specimens of intermediate colouration, inhabits the Sea of Japan.